Exploring the Social Reinforcing Value of Brushing in Equine-Assisted Services: A Comparative Study with Food Reinforcement - Schroeder, Katy; Arant, Megan; Hekkert, Cameron; Protopopova, Alexandra (Human-Animal Interactions, 2023)
Brushing is one of the most common human-horse interactions in Equine-Assisted Services (EAS). Previous research has shown both positive and negative effects of brushing on horses’ behavior and physiological states. One of the primary reasons horses are included in services such as mental and behavioral healthcare is to provide human clients with positive relational experiences; however, more empirical research is needed to determine if horses also receive socially derived benefits from their interactions with human clients. Therefore, we set out to determine whether brushing can function as a social reinforcer for horses utilized in EAS in comparison to food reinforcement. Six EAS horses from a university-based Premier Accredited Professional Association of Therapeutic Horsemanship, International center in the Southwestern Region of the United States participated in a single-subject reversal ABCABC design experiment, in which stimuli (A: Brushing, B: Food, and C: Control [Extinction]) were provided contingent on an arbitrary behavior (nose touch to the experimenter’s closed fist). All horses exhibited maximal or near-maximal responding in the food condition, but low responding in the brushing and control conditions. Data indicated that brushing was not an effective reinforcer for horses compared to food, and this could suggest brushing is a low-value reinforcer. Alternatively, it is possible to access to food at relatively short intervals in time during the experiment may have impacted the reinforcing value of brushing. Human-animal interaction proponents are increasingly calling attention to the need to ensure that equine-inclusive healthcare services address horse welfare, including the promotion of positive welfare experiences. Results from this study support the need for more research on identifying optimal interactions that can promote mutual benefits to both humans and horses participating in EAS.